2020
DOI: 10.3390/w12041026
|View full text |Cite
|
Sign up to set email alerts
|

Predicting River Embankment Failure Caused by Toe Scour Considering 1D and 2D Hydraulic Models: A Case Study of Da-An River, Taiwan

Abstract: Physically based numerical models can predict scour depth at embankments located in bend reaches. However, methodologies for utilizing these numerical models to assess the risk of reinforced concrete embankment failure are rarely investigated. Therefore, a new assessment methodology is proposed to predict the riverbank failure caused by bend scour. The methodology is primarily based on a bend scour simulation model that integrates a one-dimensional (1D) hydraulic model, a two-dimensional (2D) hydrodynamic fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Towards the investigation of Manning's n roughness coefficient estimation followed by the sensitivity analysis of floods using different hydraulic/hydrodynamic modeling approaches (1D, 2D, 1D/2D), several methodological approaches followed (Figure 1 According to the paragraphs mentioned above, it can be concluded that the objective determination of roughness coefficient in river flood modeling remains a crucial issue. Moreover, sensitivity analysis in flood inundation modeling using different hydraulic modeling approaches and/or combined with spatially distributed roughness coefficient maps is a subject that still concerns the scientific community [40][41][42][43]. The main purpose of this paper is to present an objective way to determine Manning's n roughness values, remotely-sensed estimated, and indicate how the changes in those values may affect a flood extent.…”
Section: Methodsmentioning
confidence: 99%
“…Towards the investigation of Manning's n roughness coefficient estimation followed by the sensitivity analysis of floods using different hydraulic/hydrodynamic modeling approaches (1D, 2D, 1D/2D), several methodological approaches followed (Figure 1 According to the paragraphs mentioned above, it can be concluded that the objective determination of roughness coefficient in river flood modeling remains a crucial issue. Moreover, sensitivity analysis in flood inundation modeling using different hydraulic modeling approaches and/or combined with spatially distributed roughness coefficient maps is a subject that still concerns the scientific community [40][41][42][43]. The main purpose of this paper is to present an objective way to determine Manning's n roughness values, remotely-sensed estimated, and indicate how the changes in those values may affect a flood extent.…”
Section: Methodsmentioning
confidence: 99%